Acetaminophen and Acetylsalicylic Acid Exposure in a Preterm Infant after Maternal Overdose - Pavlek, Leeann; Kraft, Monica; Simmons, Caitlyn; Ryan, Mary; Prusakov, Pavel; Campbell, Amanda; Brandehoff, Nicklaus; Ng, Patrick C.; Russell, Jason; Ciciora, Steven L.; Fathi, Omid (American Journal of Perinatology, 2019)
Here, we review the case of a 26 1/7 weeks' gestation premature female infant born to a mother who intentionally ingested a large quantity of Tylenol, aspirin, quetiapine, and prenatal vitamins. The neonate subsequently had markedly elevated levels of both Tylenol and aspirin when checked on the first day of life. While overall clinically stable, the neonate did demonstrate coagulopathy as evidenced by abnormal coagulation studies. Both poison control and a pediatric gastroenterologist/hepatologist were consulted. She successfully tolerated a course of N-acetylcysteine; her subsequent Tylenol level was markedly decreased and the neonate exhibited no further effects of toxicity. The salicylate level decreased on its own accord. To our knowledge, this is the first report of a neonate at 26 weeks' gestation that has been successfully managed for supratherapeutic concentrations of acetaminophen and acetylsalicylic acid secondary to maternal ingestion. While rare, this case may serve as a reference for the effectiveness of N-acetylcysteine in premature infants in such instances.
Keywords: acetaminophen; aspirin; neonate; premature; toxicity; N-acetylcysteine